2006
DOI: 10.1021/jp065490h
|View full text |Cite
|
Sign up to set email alerts
|

Modified Lithium Borohydrides for Reversible Hydrogen Storage (2)

Abstract: This paper reports the results of the effort to destabilize lithium borohydride for reversible hydrogen storage. Various metals, metal hydrides, and metal chlorides were selected and evaluated as destabilization agents for reducing dehydriding temperatures and improving dehydriding/rehydriding reversibility. The most effective material was LiBH4 + 0.2MgCl2 + 0.1TiCl3 which starts desorbing 5 wt % of hydrogen at 60 degrees C and can be rehydrogenated to 4.5 wt % at 600 degrees C and 70 bar. X-ray diffraction an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
145
1
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(153 citation statements)
references
References 9 publications
5
145
1
2
Order By: Relevance
“…The phenomenon of hydrogenation agrees well with that presented in Fig. 2 where the onset temperatures of TiF 3 and TiCl 3 doped mixtures are [7,22] or MgH 2 [23] system. The times to full dehydrogenation are 4000 s and 6000 s respectively.…”
Section: Absorptionedesorption Kinetics For Ti-doped Lih/ Mgb 2 Mixturessupporting
confidence: 89%
See 1 more Smart Citation
“…The phenomenon of hydrogenation agrees well with that presented in Fig. 2 where the onset temperatures of TiF 3 and TiCl 3 doped mixtures are [7,22] or MgH 2 [23] system. The times to full dehydrogenation are 4000 s and 6000 s respectively.…”
Section: Absorptionedesorption Kinetics For Ti-doped Lih/ Mgb 2 Mixturessupporting
confidence: 89%
“…Zü ttel et al found that SiO 2 helps to decompose LiBH 4 and liberate large amount (9 wt.%) of hydrogen from a temperature of 200 C [4,5]. Au et al showed that some transition metal oxides or chlorides are able to decompose LiBH 4 [6,7]. The reverse hydrogenation is even feasible for some modified complex systems as shown by Vajo et al with the system LiBH 4 þ MgH 2 [8].…”
Section: Introductionmentioning
confidence: 99%
“…Since Bogdanovic et al found that the addition of Ti-based compounds significantly promoted the dehydrogenation-rehydrogenation reactions of NaAlH 4 [193], the development of complex hydrides for hydrogen storage has significantly increased. Stimulated by this finding, a large number of additives from oxides, halides, metals, and carbon-based materials to M(BH 4 ) n have been examined [19,20,58,87,101,130,144,150,161,168,170,171,191,[194][195][196][197][198][199][200][201][202][203][204][205][206][207][208][209][210]; the corresponding dehydrogenation and rehydrogenation properties are summarized in Table 5. For instance, the most effective additive for LiBH 4 was found to be the mixture of 0.2 MgCl 2 + 0.1 TiCl 3 , in which approximately 5 mass% of hydrogen was released from 333 K and 4.5 mass% of hydrogen was rehydrogenated at 873 K in 7 MPa H 2 [195].…”
Section: Promoting Kineticsmentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12][13][14][15] These strategies generally led to an improvement in their hydrogen sorption properties. However, for practical application further improvement of these materials is required.…”
Section: Introductionmentioning
confidence: 99%